2007
DOI: 10.1021/jf071432x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Proteins and Peptides as Tools for Studying IgE Reactivity with Low-Molecular-Weight Glutenin Subunits in Some Wheat Allergies

Abstract: Two genes of wheat low-molecular-weight glutenin subunits (LMW-GS), B16 and P73, were cloned and expressed in E. coli. They were homologous to proteins encoded respectively at Glu-B3 and Glu-D3 loci. The N-terminal and C-terminal halves of B16 (NB16 and B16C) and the two chimeras combining the halves of the two genes (B16-P73 and P73- B16) were also expressed. All these constructs were compared for their reactivity with IgE from 24 patients suffering from different forms of wheat allergies. The results confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 31 publications
4
24
0
Order By: Relevance
“…These results have confirmed the immunoreactivity of α, β and γ gliadins, previously reported in our study that tested purified gliadin fractions by ELISA [28]. The current work is also consistent with the results obtained by other authors who reported allergenicity of α, β and γ gliadins in atopic dermatitis, and LMW glutenins in baker's asthma [20,29,30]. The study of Maruyama et al [31] determined their relative reactivity in the following order: glutenins>gliadins>NGP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results have confirmed the immunoreactivity of α, β and γ gliadins, previously reported in our study that tested purified gliadin fractions by ELISA [28]. The current work is also consistent with the results obtained by other authors who reported allergenicity of α, β and γ gliadins in atopic dermatitis, and LMW glutenins in baker's asthma [20,29,30]. The study of Maruyama et al [31] determined their relative reactivity in the following order: glutenins>gliadins>NGP.…”
Section: Discussionsupporting
confidence: 92%
“…In turn, ω-1.2 gliadins were evidenced to be allergenic for patients with atopic dermatitis [19]. LMW glutenins play an important role in the development of immediate hypersensitivity to hydrolyzed wheat proteins (IHHWPs) baker's asthma, atopic dermatitis and EIWA [18,20]. Battais et al showed elevated levels of IgE antibodies against all GP in the sera of 28 patients with atopic dermatitis, asthma, urticaria and eczema, which suggested that these proteins were important factors contributing to disease development [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…LMW-GS B16 and P73 have been previously described [15]. They can be considered as models for LMW-GS coded by wheat genomes B and D, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…One gene called A12 was obtained. The cloning of the two recombinant LMW-GS, called LMW-GS B16 and P73, has already been described [15]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation